Strategi Implementasi Program Smart Indonesia: Strategi Pelaksanaan Kebijakan Program Smart Indonesia - Rachmahnia, Lia; Choiriyah, Ilmi Usrotin (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the implementation of the Smart Indonesia Program (PIP) at Buduran 1 State Vocational School in Sidoarjo Regency using a qualitative descriptive research method. Through interviews, observation, and documentation, data was collected from key informants, including the school principal, administrative staff, and program beneficiaries. The study reveals that PIP is effectively communicated through special events and verbal interactions with students. The school has provided sufficient facilities, such as computers and wifi, and benefits from supportive factors like parental involvement and collaboration between Guidance and Counseling teachers. However, challenges arise from communication gaps between funding agencies and schools, impacting data accuracy. The findings underscore the need for streamlined communication channels to optimize PIP implementation. Highlight : Effective Communication: The study emphasizes the importance of special events and verbal communication in disseminating information about the Smart Indonesia Program, ensuring awareness among students and stakeholders. Facility Provision: Buduran 1 State Vocational School's proactive approach in providing adequate facilities, including computers and wifi, contributes to the successful implementation of the Smart Indonesia Program. Communication Challenges: The research highlights the inhibiting factor of communication gaps between channeling agencies and schools, impacting fund collection and data accuracy, underscoring the need for improved communication channels. Keywords: Smart Indonesia Program, Vocational Education, Implementation Analysis, Communication, Facilities